Engineering Subwavelength Nanoantennas in the Visible by Employing Resonant Anisotropic Nanospheroids - G. D. Kolezas; G. P. Zouros; K. L. Tsakmakidis (IEEE Journal of Selected Topics in Quantum Electronics, 2019)
We analyze the engineering of subwavelength nanoantennas composed of anisotropic nanospheroids, for the development of photonic devices. Instead of using conventional isotropic dielectrics, we introduce resonant anisotropic nanoparticles, allowing for shifting Kerker condition points further inside the visible. To address this study, we construct a perturbation-based discrete eigenfunction method, for the electromagnetic scattering of a plane wave by a prolate or oblate uniaxial anisotropic spheroid. The method is fast and yields the solution for the bistatic radar and total scattering cross sections, which is valid for small eccentricities of the spheroid. The validity of this technique is verified by the alternative general purpose discrete dipole approximation method. We investigate the engineering of subwavelength nanoantennas due to material and geometry shaping, like the change of anisotropy type, anisotropy ratio, and deviation of the nanoantenna from sphericity. © 1995-2012 IEEE.
cited By 3